An Elementary Proof of Gilbreaths Conjecture - Sazegar, Hashem (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Given the fact that the Gilbreath's Conjecture has been a major topic of research in Aritmatic progression for well over a Century,and as bellow: 2 3 5 7 11 13 17 19 23 29 31 37 41 43 47 53 59 61 1 2 2 4 2 4 2 4 6 2 6 4 2 4 6 6 2 1 0 2 2 2 2 2 2 4 4 2 2 2 2 0 4 1 2 0 0 0 0 0 2 0 2 0 0 0 2 4 1 2 0 0 0 0 2 2 2 2 0 0 2 2 1 2 0 0 0 2 0 0 0 2 0 2 0 1 2 0 0 2 2 0 0 2 2 2 2 1 2 0 2 0 2 0 2 0 0 0 1 2 2 2 2 2 2 2 0 0 1 0 0 0 0 0 0 2 0 1 0 0 0 0 0 2 2 1 0 0 0 0 2 0 1 0 0 0 2 2 1 0 0 2 0 1 0 2 2 1 2 0 1 2 1 The Gilbreath's conjecture in a way as easy and comprehensive as possible. He proposed that these differences, when calculated repetitively and left as bsolute values, would always result in a row of numbers beginning with 1,In this paper we bring elementary proof for this conjecture.